Museo de Artes Visuales - Coleccion Santa Cruz - Yaconi. - Ivelic, Milan; Santa Cruz, Manuel (Santiago de Chile : Museo de Artes Visuales, 2001)
Abelli, Christian ; Alamos, Tatiana ; Aldunate, Carmen ; Altamirano, Carlos ; Antunez, Nemesio ; Aranguiz, Santiago ; Arestizabal, German ; Assler, Federico ; Balmes, José ; Banderas, Ernesto ; Barcia, Augusto ; Barra, Oscar ; Barreda, Ernesto ; Barrios, Gracia ; Bascuñan, Roberto ; Basso, José Esteban ; Beltran, Ciro ; Bendersky, Jaime ; Benmayor, Samy ; Borja Huidobro ; Bozinovic, Pamela ; Bravo, Claudio ; Bru, Roser ; Cabezas, Rodrigo ; Cadiz, Ruperto ; Calderon, Hector ; Canto, Patricia del ; Carreno, Mario ; Carvajal, Nicole ; Castillo, Sergio ; Castro, Aura ; Cerda, Francisca ; Cienfuegos, Gonzalo ; Codocedo, Victor Hugo ; Colvin, Marta ; Copello, Francisco ; Corcuera, Francisco ; Correa, Marcela ; Cristi, Ximena ; Cruz, Jaime ; Cruz, Valentina ; Daiber, Ivan ; Davila, Juan ; Diaz Fleming, Juan ; Diaz, Gonzalo ; Dittborn, Eugenio ; Dominguez, Irene ; Dominguez, Pablo ; Doudtchitzky, Dinora ; Downey, Juan ; Duclos, Arturo ; Edwards, Roberto ; Egenau, Juan ; Errázuriz, Paz ; Fernandez, Carlos ; Fernández, José Gabriel ; Figueroa, Patricia ; Frigerio, Ismael ; Gacitúa, Oscar ; Gajardo, José Vicente ; Galaz, Gaspar ; Gana, Andres ; Garafulic, Lily ; Garcia Chibbaro, José ; Garcia de la Sierra, Eduardo ; Garreaud, Eduardo ; Garreton, Sebastian ; Gatica, Omar ; Gazitua, Francisco ; Gazitua, Teresa ; Gazmuri, Hernan ; Geisse, Roberto ; Gomez, Mario ; Gonzalez, Luis Alberto ; Gonzalez, Nury ; Harnecker, Ines ; Huidobro, Matilde ; Ilabaca, Gonzalez ; Irarrazabal, Mario ; Israel, Patricia ; Jaar, Alfredo ; Kemper, Claudia ; Klotz, Isabel ; Lagos, Nelson ; Landea, Gonzalo ; Larrain, Marcelo ; Laval, Gaston ; Lay, Sergio ; Lazo, Felix ; Lefever, Eva ; Leon, Jaime ; Leppe, Carlos ; Leyton, Monica ; Lira, Benjamin ; Lira, Paz ; Maffei, Ricardo ; etc.
Spaans & Engels
Museo de Artes Visuales - Coleccion Santa Cruz - Yaconi, Santiago de Chile, Abril 2001
boek